THE MANAGEMENT OF CURRICULUM IN INTEGRATED-ISLAMIC ELEMENTARY SCHOOL: FACILITATING QURAN LEARNING - Ahmad Fathur Rosyadi; Subiyantoro (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2021)
This research discusses the management of the Quran learning curriculum at Integrated-Islamic Elementary School of Luqman Al-Hakim Yogyakarta. This research is field research with a descriptive qualitative approach. The research data was taken from various scientific writings, school curriculum documents, field observation notes, and interviewees determined by non-probability sampling and purposive sampling. The data were tested by data triangulation and analyzed using the Miles & Huberman technique: (a) data reduction, (b) data presentation, (c) conclusion and verification. The results: The Quran learning curriculum is a set of educational program plans, target achievements, and learning strategies that are carried out so that students read the Quran Tartil and have three juz of memorization. The curriculum management process includes planning, organizing, implementing, and evaluating.